Purchasing Power of Farmers - Challenges and Opportunities in Indian Agriculture - Pabalkar, Vanishree; Morey, Rashmy; Rai, Shivanand (Asian Journal of Agriculture and Rural Development, 2020)
The objective of the study is to analyse the farmer’s financial condition and to understand the challenges faced in exhibiting the power of purchasing. The study indicates that there is abundant scope to improve the agriculture and financial condition of farmers in the entire country. The primary input for the study has been collected by an informal interview with focus groups of various populations of farmers, retailers, distributors, opinion leaders, and government officials to find out the status of agriculture and financial conditions of farmers. The total sample size was 500 farmers for empirical analysis.